Genetic diversity of alpha and betacoronaviruses in cave and temple-roosting bats in Vientiane Province, Lao PDR - Illich Manfred Mombo; Novy Charel Bobouaka Bonguili; Nicola Gasperini; Arisa Chandarak; Thida Xaiyaphoumi; Pauline Brault; Oceane Rieu; Phimpha Paboriboune; Eric Leroy; Fabien Roch Niama; Sabrina Locatelli (PLoS ONE, 2026)
The emergence of MERS-CoV, SARS-CoV-1, and SARS-CoV-2 highlights the significant public health and economic threats posed by coronaviruses. In Lao PDR, SARS-CoV-2-related bat coronaviruses capable of binding to human ACE2 receptors have been found in northern regions, but little is known about coronavirus diversity in anthropized environments like temples. This study investigated coronavirus circulation, diversity, and prevalence in bats from caves and temples in Vientiane Province, Lao PDR. A total of 648 guano samples (505 Chaerephon plicatus , 100 Hipposideros spp., 43 Taphozous spp.) were collected between December 2022 and June 2023 and screened using pan-coronavirus RT-PCR approach. The overall positivity rate was 17.28%, significantly higher in caves (18.8%) than temples (4.41%) (p = 0.003). C. plicatus showed the highest positivity rate (21.38%), followed by Hipposideros spp. 4%, while Taphozous spp. were negative. Phylogenetic analysis revealed diverse coronavirus lineages within Alphacoronavirus (80.4%) and Betacoronavirus (19.6%) genera. Although none were closely related to known human pathogens, coronaviruses of Decacovirus genus related to Chinese bat viruses and Pedacovirus genus similar to porcine epidemic diarrhea virus (PEDV) were detected. Unclassified betacoronaviruses identified were also related to viruses from C. plicatus in Thailand. This study provides valuable insights into coronavirus circulation in both natural and anthropized environments. The detection of PEDV-like viruses underlines the need for continued surveillance at the human-bat interface, where activities like guano harvesting and temple visits increase contacts. Further genomic and functional studies would enhance our understanding of their evolutionary relationships and potential for further cross-species transmission.